Assessment of mobile screen time, sleep quality, and reaction time in young adults with premenstrual dysphoric disorder - Doreswamy Kanakaiah; Varun Manjunath; Venkatesha R; Yashica Gowda R; Sai Sailesh Kumar Goothy; Sadgunothama Goud Kamparaj; Anitha Lakshmi (Asian Journal of Medical Sciences)
Background: Premenstrual syndrome is observed in the late luteal phase of the menstrual cycle. However, the studies related to the assessment of screen time, sleep quality, and reaction time (RT), in young adults with premenstrual dysphoric disorder are sparse in the Indian scenario. Hence, the present study was undertaken.